Pembuatan Biodiesel Dari Sawit Off Grade Dengan Menggunakan Katalis Zno Komersial Pada Proses Transesterifikasi - Yulva Gemy; Sri Helianty; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Vegetable oil with high FFA derived from off grade palm oil can be used as raw material for making biodiesel. ZnO is currently developed as a heterogeneous catalyst in the reaction of biodiesel production. This research aimed to produce biodiesel from low-quality raw materials and determine the effectiveness of the process by looking at the effect of process conditions such as reaction temperature, mole ratio and catalyst concentration on the yield of biodiesel. The process of making biodiesel is done with two stages of the reaction of esterification and transesterification reactions. Esterification reaction carried out at a temperature of 65oC, the mole ratio of oil: methanol 1:12, and 1% catalyst concentration. Variations in operating conditions transesterification reaction include reaction temperature (45oC, 55oC, 65oC), the mole ratio of oil: methanol (1:10, 1:14, and 1:18), and catalyst concentration (0.5%, 1%, and 2% / w). The highest yield of biodiesel obtained as much as 94.26% under the conditions of reaction temperature of 65oC, the mole ratio of oil: methanol 1:18, and 2% of ZnO catalyst concentration. The characteristics of biodiesel produced in the form of density, kinematic viscosity, acid number and flash point are in according to the standards of Indonesian biodiesel.Keywords: biodiesel, esterification, off grade palm oil, transesterificationi, ZnO